Peripheral talus fractures: epidemiology and short-term outcomes - Sakaki, Marcos; Bergamasco, Jordanna; Pinheiro, Lais; Rosa e Silva, Caio; Missima, Kenji (Journal of the Foot & Ankle, 2021)
Objective: To present the epidemiology and assess short-term clinical and radiological outcomes of peripheral talus fractures treated between 2013 and 2019 at a secondary hospital. Methods: This is a retrospective study based on a series of 21 cases of peripheral talus fractures. Out of these 21 cases, 11 underwent functional assessment using the ankle-hindfoot scale of the American Orthopaedic Foot and Ankle Society (AOFAS) and radiological assessment after a mean period of 24.5 months. Results: Regarding the epidemiology of the 21 reported cases, the mean age was 28.7 years and 76.2% of the patients were male. The left foot was affected in 71.4% of the cases, and the most frequent type of trauma was motorcycle accident (47.6%); 23.8% of the cases had open fractures. Complete peritalar dislocation occurred in 38.0% of the cases and the most common fracture was that of the lateral process of the talus, in 42.8% of the cases. Eleven patients returned for reassessment and presented a mean AOFAS score of 80.9 points. All fractures were consolidated at the moment of assessment, and one of them progressed to subtalar and talonavicular osteoarthritis, requiring triple arthrodesis. Conclusion: The peripheral fractures studied here were caused by high-energy traumas with open fractures in one-quarter of the cases and were frequently associated with other fractures. The short-term functional outcome is good but has potential for severe complications such as stiffness and persistent pain. Level of Evidence IV, Therapeutic Studies; Case Series.